Anticancer activity of dark chocolate mediated zinc oxide nanoparticles in HT-29 colon cancer cell lines – An in vitro study - Khushi Jain D,; Nitheesh S,; Parameswari Royapuram Parthasarathy,; Geetha R V, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Colorectal cancer is a prevalent malignancy characterized by the transformation of normal cells in the colon or rectum into cancerous cells. Dark chocolate-mediated zinc oxide nanoparticles (DC-ZnO NPs) have emerged as a promising therapeutic approach due to their combined antioxidant and cytotoxic properties. This study investigates the anti-cancer activity of DC-ZnO NPs on HT-29 colon cancer cells, focusing on apoptosis induction, cytotoxicity, and morphological alterations. Methods: DC-ZnO NPs were synthesized using avocado seed extract and characterized by their physicochemical properties. HT-29 colon cancer cells were treated with varying concentrations of DC-ZnO NPs, and cell viability was assessed using cytotoxicity assays. Apoptosis was evaluated through dual staining with ethidium bromide (EtBr) and acridine orange (AO). Morphological changes in the cells were observed using fluorescence microscopy to identify features associated with early apoptosis. Results: Cytotoxicity assays demonstrated a substantial reduction in cell viability at this concentration. Dose-dependent decrease in the cell viability was observed between concentrations 10-100µg/mL. Morphological analysis at 80µg/mL revealed characteristic apoptotic changes, including cell shrinkage and membrane blebbing. Further, treatment with 80 µg/mL DC-ZnO NPs resulted in significant induction of early apoptosis, as evidenced by the yellowish-green staining of apoptotic cells. These findings indicate that DC-ZnO NPs effectively induce apoptosis in HT-29 cells, enhancing their potential as an anti-cancer therapeutic. Conclusion: DC-ZnO nanoparticles exhibit potent anti-cancer activity in HT-29 colon cancer cells by inducing apoptosis and causing significant cytotoxic effects. The dual action of dark chocolate and ZnO NPs provides a promising approach for colorectal cancer treatment. Further research is needed to explore the detailed mechanisms and assess in vivo efficacy to fully establish the therapeutic potential of DC-ZnO NPs.